Clinical outcome and bowel function after surgical treatment in Hirschsprung's disease - Maryam Khazdouz; Majid Sezavar; Bahareh Imani; Hossein Akhavan; Alireza Babapour; Gholamreza Khademi (Wolters Kluwer Medknow Publications, 2015)
Background: Bowel function has been reported to be adversely affected following surgery in cases of Hirschsprung. We retrospectively studied both the clinical outcome and bowel function status following surgery in patients diagnosed with Hirschprung's disease (HD). 161 cases, who underwent pull-through operations for HD in Sheikh Pediatric Tertiary Centre, Mashhad, Iran. The specified time bracket spanned between 2006 and 2011. Materials and Methods: Data was extracted from Health Information System with the aim of investigating patients for both short and long-term gastrointestinal (GI) complications after surgery bases in addition to the concurrence of any associated anomalies. Three main procedures were analysed in this respect (Swenson, Duhamel and Soave). Results: In a study of 96 (59%) boys and 65 (40.3%) girls, mortality rate was reported to be 15.5% (15 males and 10 females). A considerable majority of almost three fourths were detected with both early and late GI complications after surgery. The latter mainly included constipation (30.8%), incontinence (19.8%), enterocolitis (8%), diarrhea (11%) in a declining order of incidence. Down syndrome and others HD-associated anomalies were detected in 3.7% and 24.3% of cases respectively. Conclusions: Constipation and foecal incontinence were the most prevalent postoperative complications, which were reported almost as frequent in other studies. Yet, Enterocolitis, was reported slightly less in prevalence. Also mortality rates were considerably higher, compared to developed nations.